Simultaneous Estimation of Ranitidine Hydrochloride and Ondansetron Hydrochloride by Reverse Phase High Performance Liquid Chromatography - M. Patel, Nirav; Fursule, R.A.; Shirkhedkar, A.A.; Talele, G.S. (Asian Journal of Chemistry, 2010)
A simple, precise, fast, reproducible and selective reverse phase HPLC method has been developed for the simultaneous estimation of ranitidine hydrochloride and ondansetron hydrochloride from tablet. This was resolved by using mobile phase (methanol and 0.05 M phosphate buffer in a ratio 60 : 40 and pH 5.8 was adjusted by triethylamine) at a flow rate of 1.0 mL/min on an isocratic HPLC system consisting of LC-10 AT liquid pump, SPD-10A UV-Vis detector, an ODS C-18 RP column (250 x 4.6 mm) at a wavelength of 310 nm. The linear dynamic range for ranitidine hydrochloride was 35.0 to 195.0 μg/mL and ondansetron hydrochloride was 1.0 to 5.0 μg/mL is obtained by this method.